The Ecology Features of Tick-Borne Encephalitis Virus of European Subtype in Siberia - I. V. Kozlova; S. E. Tkachev; Yu. S. Savinova; T. V. Demina; E. K. Doroshchenko; O. V. Lisak; Yu. P. Dzhioev; O. V. Suntsova; M. M. Verkhozina; A. I. Paramonov; V. I. Zlobin; N. V. Tikunova; et al. (Эпидемиология и вакцинопрофилактика)
The aim of the study was to determine the ecology features of tick-borne encephalitis virus (TBEV) of European subtype circulating in Siberia. The strains of European subtype TBEV from Siberia were isolated in areas with different terrain types - from the plains to the midlands. The strains isolation areas differed in variety of landscapes, flora and fauna and were characterized by the presence of sharp-continental, or in some places - quite harsh climate. The composition of the main vectors and reservoir hosts of TBEV of European subtype in Siberia has its own features and is significantly different from that one in Europe. However, in spite of this, the homology of TBEV strains of European subtype isolated in different parts of habitat range of the virus from the Scandinavian countries in the West to its Eastern borders is much higher than the homology level degree of TBEV strains of FarEastern and Siberian subtypes.